ANALISIS DETERMINAN PEMBENTUK KAPASITAS FISKAL DAERAH PROVINSI GORONTALO TAHUN 2011 - 2020 - Martin Lutther, (2023)
Regional fiscal capacity is an indicator to measure the ability of local governments to manage their own finances. Measures of a region's fiscal capacity generally depend on the quality of government policies used to increase and manage regional revenue streams for programs and services provided to the public. Given the complete dependence of many regions on the central government, there is a need to monitor the fiscal of existing local governments. The purpose of this study was to determine the effect of regional local own-source revenue, intergovernmental transfer, other lawful local revenue, and personnel expenditure on the formation of regional fiscal capacity in the Gorontalo Province. The object of the study is the financial report of Gorontalo Province with a test sample of the existing regency/city government budget realization report covering the research test year from 2010-2020. Panel data regression analyst techniques, classical assumption tests, and significance tests are data analysis techniques used in this study. The significance test uses the t test, F test, and coefficient of determination (R2). To reach the research axiom, the researcher also tested the classical assumptions test in the research. The method of findings that fixed effect models are the best for subsequent analysis of findings. The results of the study indicate that the variables of local own-source revenue, intergovernmental transfer, and personnel expenditure have a positive and significant effect, while other variables other lawful local revenue do not significantly affect the establishment of regional fiscal capacity in the region of Gorontalo Province.